Pemberdayaan Masyarakat melalui Pembentukan Forum Ibu Hamil No Anemia No Stunting - Aminin, Fidyah; Mukodri, Dewi Mey Lestanti; Erda, Zulya; Putri, Sabtini Ika; Jannah, Rawdatul (Poltekes Kemenkes Tanjungpinang, 2024)
Stunting is a critical issue that needs to be addressed. The lack of independence among rural communities, particularly pregnant women and community health cadres, in preventing anaemia and stunting, as well as the absence of a dedicated forum for such activities, highlights the need to establish the For U No Anemia No Stunting (For U NAS) forum. This community engagement program aims to form For U NAS as a measure to prevent anemia and stunting in Kampung Bugis. The methods include establishing the forum, providing health education using the Si NaNing application, modules, and healthy kitchen demonstrations, as well as conducting pre-test and post-test evaluations. The results demonstrate the successful establishment of For U NAS and a significant increase in pregnant women's knowledge about anemia and stunting after the intervention. This forum serves as a platform for education, discussion, and social support, strengthening the independence of pregnant women. In conclusion, the formation of this forum has effectively improved pregnant women's knowledge of preventing anemia and stunting. This initiative is likely to continue with the development of peer support groups to enhance education efforts in the future.